Rational approaches to the therapy of nosocomial infections caused by gram-positive microorganisms in cancer p - V. V. Aginova; N. V. Dmitrieva; Z. V. Grigorievskaya; I. N. Petukhova; N. S. Bagirova; I. V. Tereshchenko; I. А. Klyuchnikova (Сибирский онкологический журнал, 2017)
Nosocomial infections caused by gram-positive organisms, including Staphylococcus aureus and enterococci (Enterococcus faecium and Enterococcus faecalis) are steadily increasing in almost all clinics around the world. Cancer patients have a higher risk of hospital-acquired infections than non-cancer patients. Cancer patients are immunosuppressed due to increased use of broad-spectrum antibiotics and chemotherapy drugs, radiation therapy, surgery and use of steroids. This paper presents an analysis of resistance of gram-positive bacterial pathogens to antimicrobial agents to determine treatment strategy for cancer patients.